Autopercepção da saúde e da qualidade de vida, desempenho funcional e prática de atividade física entre idosos residentes em município rural no interior do Brasil - Barbosa, Renata da Costa (2021)
Aging can lead to greater dependence on the individual, compromising functional performance, self-perception of health and quality of life. A physically active lifestyle can provide the maintenance of functionality and improve the quality of life and health of the elderly. Behavior and lifestyle habits may be influenced by the location where the elderly person lives. Understanding how elderly people living in rural municipalities perceive their health and quality of life can provide subsidies to better help these populations. Objective: To analyze the associations between self-perceived health and quality of life with functional performance and the practice of physical activity among elderly people living in rural municipality in Brazil. Method: Analytical cross-sectional population-based study. Individuals aged 60 years or more, noninstitutionalized, living in a rural municipality in the interior of Goiás were included. Sociodemographic, anthropometric and lifestyle variables were evaluated. In addition, functional performance was assessed using the Timed Up and Go (TUG) test and physical activity practice using the International Physical Activity Questionnaire (IPAQ). As outcome variables, self-perceived health and quality of life were assessed using the Bref and Old World Health Organization Quality of Life Instruments questionnaires (WHOQOL BREF and WHOQOL OLD). Data were obtained during a home visit, by an interview. To assess the association of the variables of interest, Pearson's chi-square test, Fisher's exact test and the Wilcoxon sign were used. Results: The study included 142 elderly people with a mean age of 72.4 (±8.0) years. More than half were classified as sufficiently active (66.9%), among these, 55.8% performed leisure activities, the vast majority were independent in activities of daily living (87.3%), with regular/good quality of life (average overall score: 3.6±0.3) and, respectively, 57.7% and 64.1% had self-perceived health and quality of life. Elderly people with poor or very poor self-perceived health had regular self-perceived quality of life (63.6%), individuals aged 80 years and over had lower self-perception of quality of life compared to others. There was an association of self-rated health with the practice of physical activity and functional performance. However, no associations were found with the type of physical activity. It was found that 50.0% of the elderly who were insufficiently xvii Abstract 18 active and independent perceived their health positively. Of the insufficiently active and dependent elderly, 35.7% had poor/very bad and good/very good self-perceived health. Conclusions: Elderly people living in a rural municipality showed good or very good perception of health and quality of life, independent in their activities of daily living and sufficiently active. Self-perceived health was associated with quality of life, functional performance and physical activity practice, not being associated with the other study variables.